Modification of media formulation for enhancing production of extracellular polysaccharides by porphyridium cruentum - Yaakop, Amira Suriaty (2013)
The red microalgae Porphyridium cruentum produce many valuable compounds such as extracellular polysaccharides (EPS) that are extensively used in the industry. In this study modification of media formulation for optimal production of EPS from Porphyridium cruentum was carried out by varying nitrate, sulfate and glucose concentrations in the Jones 1962 media. Different concentration of each nutrient was used in the media formulation. For nitrate, the highest concentration provided in the medium at 50 mM showed the highest growth rate and EPS production, but by inhibiting the nitrate concentration, the growth is reduced while the production of EPS is increased as when a high concentration of nitrate was provided to the medium. For sulfate, increasing concentration in the media showed great decrease in growth rate, but increasing EPS production, the highest production of EPS was at 50 mM which was the highest concentration of sulfate provided in the media modification. Addition of glucose in the medium on the other hand substantially increased the growth rate and the biomass production but as the glucose concentration kept on increasing, it also inhibited the production of EPS by the algae. The growth rate of the algae did not correlate with the EPS production. The result showed that high concentration of glucose and low concentration of nitrate and sulfate inhibited the production of EPS by the microalgae and in order to increase the EPS production, medium without nitrate or a very high concentration of nitrate or and sulfate must be provided. Therefore, the optimum medium formulation for optimal growth and EPS production by Porphyridium cruentum is at either 20 mM of nitrate or without nitrate at all, 50 mM of sulfate and 0.5% (w/v) of glucose. The compositions of the EPS were also confirmed by using HPLC that showed the composition of glucose, galactose and xylose of the EPS.